High-strength composite board
By using modified ramie fiber and modified magnesium fiber in composite sheets, combined with epoxy resin and calcium silicate boards, the shortcomings in flame retardant performance and environmental protection of existing composite sheets are solved, and a comprehensive composite sheet with high strength and good flame retardant is achieved.
Patent Information
- Application Number
- CN202411864560.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
While existing composite panels enhance flame retardant performance, it is difficult to achieve environmentally friendly comprehensive panel design. Phosphorus and halogen flame retardants are prone to environmental pollution.
High-strength composite sheets are prepared by using composite fibers including modified ramie fibers and modified magnesium fibers through ultraviolet grafting and other chemical modification methods, combined with epoxy resin and calcium silicate plates.
It improves the mechanical properties and impact resistance of composite sheets, and at the same time shows good flame retardant effects during combustion, avoiding environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite plates, and in particular to a high-strength composite plate. Background Art
[0002] Composite panels are made of two or more materials with different properties combined by physical or chemical methods to form panels with new properties. With the advancement of science and technology and the increasing requirements of consumers for environmental protection and new energy, composite panels are developing towards intelligence and environmental protection.
[0003] In order to enhance the flame retardant properties of composite boards, in the prior art, phosphorus-based, halogen-based and other flame retardant substances with good flame retardant properties are usually added to the raw materials when preparing the composite boards. However, phosphorus-based and halogen-based flame retardants are prone to environmental pollution. Therefore, it is necessary to improve the design of the components of the composite boards so that the composite boards become comprehensive boards with good flame retardant properties and environmental protection. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a high-strength composite plate material, which can.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high-strength composite board comprises a core layer and calcium silicate boards arranged on both sides of the core layer, wherein the components of the core layer comprise the following raw materials in parts by weight: 80-100 parts of silicate cement, 4-10 parts of foaming agent, 30-40 parts of epoxy resin, 10-20 parts of curing agent and 20-30 parts of composite fiber, wherein the composite fiber comprises modified ramie fiber and modified brucite fiber twisted together.
[0006] Preferably, the preparation method of modified ramie fiber is: S1. Take ramie fiber and soak it in 5% sodium hydroxide solution for 5 hours; S2, soaking the ramie fiber after the alkali treatment in a glycidyl acrylate grafting solution containing benzophenone for 24 hours, placing the soaked ramie fiber on a glass plate, pressing it with a glass sheet, and performing UV ultraviolet light grafting treatment; S3. The grafted ramie fiber was extracted by Soxhlet extraction for 10 hours, then treated in a 5% by volume ethylenediamine solution for 8 hours, then immersed in a 5% by volume nitric acid solution for 8 hours, and dried to obtain the modified ramie fiber.
[0007] Preferably, the preparation method of the modified brucite fiber is: S1, taking brucite fiber, adding a dispersant to disperse it, then performing ultrasonic treatment, washing it with deionized water, drying it and setting it aside; S2. Weigh 3% of the coupling agent by weight of the dry sample of brucite fiber, mix it evenly with the brucite fiber obtained in S1, and bake it in an oven at 100°C for 5 hours to obtain modified brucite fiber.
[0008] Preferably, the epoxy resin is one of bisphenol F epoxy resin, Novolac epoxy resin, bisphenol A epoxy resin or trimethylolpropane epoxy resin.
[0009] Preferably, the dispersant is sodium salt of dioctyl sulfonate succinate.
[0010] Preferably, the method for preparing the composite plate comprises the following steps: S1, weighing a foaming agent, mixing it with water to prepare a foaming aqueous solution, and preparing the mixed foaming aqueous solution into foam using a foaming machine; S2, weighing silicate cement, epoxy resin, curing agent, and composite fiber, and mixing them with the foam obtained in step S1 to obtain the core layer raw material; S3. According to the required thickness of the composite board, determine the distance between the two calcium silicate boards on the sides away from each other, fill the core layer raw materials between the two calcium silicate boards, remove the mold after the test piece is formed for 1 day, and perform a compression test after standard curing for 28 days to obtain a high-strength composite board.
[0011] Preferably, the calcium silicate board facing is the outer surface of the high-strength composite board, and the surface of the calcium silicate board close to the core layer is a rough surface.
[0012] Preferably, the mass ratio of the foaming agent to water is 1:30.
[0013] The beneficial effects of the present invention are: The ramie fiber that is grafted with glycidyl acrylate by ultraviolet light, then aminated and nitrated contains N-OH. When preparing the composite board, the modified ramie fiber reacts with the epoxy group during the composite process of the epoxy resin, and the ramie fiber and the epoxy resin are connected by chemical bonds, and the interfacial viscosity effect is improved, thereby improving the mechanical properties of the composite board, and enhancing the tensile strength and impact resistance of the composite board. In addition, after the modified ramie fiber is composited with the epoxy resin to make a composite board, there is obvious carbonization during the combustion process, which promotes the esterification of cellulose hydroxyl groups, and the generated cellulose ester decomposes into carbon, making the composite board have a good flame retardant effect.
[0014] The modified brucite fiber has good compatibility with epoxy resin and is firmly bonded. The silane-modified brucite nanofiber fills the molecular gap of epoxy resin and improves the impact resistance of the composite material. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Embodiment 1: A high-strength composite board comprises a core layer and calcium silicate boards arranged on both sides of the core layer, wherein the core layer comprises the following raw materials in parts by weight: 80 parts of silicate cement, 4 parts of foaming agent, 30 parts of epoxy resin, 10 parts of curing agent and 20 parts of composite fiber, wherein the composite fiber comprises modified ramie fiber and modified brucite fiber twisted together.
[0017] Wherein, the epoxy resin is bisphenol F epoxy resin.
[0018] The preparation method of modified ramie fiber is as follows: S1. Take ramie fiber and soak it in 5% sodium hydroxide solution for 5 hours; S2, soaking the ramie fiber after the alkali treatment in a glycidyl acrylate grafting solution containing benzophenone for 24 hours, placing the soaked ramie fiber on a glass plate, pressing it with a glass sheet, and performing UV ultraviolet light grafting treatment; S3. The grafted ramie fiber was extracted by Soxhlet extraction for 10 hours, then treated in a 5% by volume ethylenediamine solution for 8 hours, then immersed in a 5% by volume nitric acid solution for 8 hours, and dried to obtain the modified ramie fiber.
[0019] The preparation method of modified brucite fiber is: S1, taking brucite fiber, adding sodium salt of dioctyl sulfonate succinate to disperse it, then performing ultrasonic treatment, washing it with deionized water, drying it and setting it aside; S2. Weigh 3% of the coupling agent by weight of the dry sample of brucite fiber, mix it evenly with the brucite fiber obtained in S1, and bake it in an oven at 100°C for 5 hours to obtain modified brucite fiber.
[0020] The preparation method of the composite plate comprises the following steps: S1, weighing a foaming agent, mixing the foaming agent with water in a mass ratio of 1:30 to prepare a foaming aqueous solution, and preparing the mixed foaming aqueous solution into foam using a foaming machine; S2, weighing silicate cement, epoxy resin, curing agent, and composite fiber, and mixing them with the foam obtained in step S1 to obtain the core layer raw material; S3. According to the required thickness of the composite board, determine the distance between the two sides of the calcium silicate boards that are away from each other, fill the core layer raw materials between the two calcium silicate boards, remove the mold after the test piece is formed for 1 day, and perform a compression test after standard curing for 28 days to obtain a high-strength composite board; The calcium silicate board facing is the outer surface of the high-strength composite board, and the surface of the calcium silicate board close to the core layer is a rough surface.
[0021] Embodiment 2: A high-strength composite board comprises a core layer and calcium silicate boards arranged on both sides of the core layer, wherein the core layer comprises the following raw materials in parts by weight: 100 parts of silicate cement, 10 parts of foaming agent, 40 parts of epoxy resin, 20 parts of curing agent and 30 parts of composite fiber, wherein the composite fiber comprises modified ramie fiber and modified brucite fiber twisted together.
[0022] Wherein, the epoxy resin is Novolac epoxy resin.
[0023] The preparation method of modified ramie fiber is as follows: S1. Take ramie fiber and soak it in 5% sodium hydroxide solution for 5 hours; S2, soaking the ramie fiber after the alkali treatment in a glycidyl acrylate grafting solution containing benzophenone for 24 hours, placing the soaked ramie fiber on a glass plate, pressing it with a glass sheet, and performing UV ultraviolet light grafting treatment; S3. The grafted ramie fiber was extracted by Soxhlet extraction for 10 hours, then treated in a 5% by volume ethylenediamine solution for 8 hours, then immersed in a 5% by volume nitric acid solution for 8 hours, and dried to obtain the modified ramie fiber.
[0024] The preparation method of modified brucite fiber is: S1, taking brucite fiber, adding sodium salt of dioctyl sulfonate succinate to disperse it, then performing ultrasonic treatment, washing it with deionized water, drying it and setting it aside; S2. Weigh 3% of the coupling agent by weight of the dry sample of brucite fiber, mix it evenly with the brucite fiber obtained in S1, and bake it in an oven at 100°C for 5 hours to obtain modified brucite fiber.
[0025] The preparation method of the composite plate comprises the following steps: S1, weighing a foaming agent, mixing the foaming agent with water in a mass ratio of 1:30 to prepare a foaming aqueous solution, and preparing the mixed foaming aqueous solution into foam using a foaming machine; S2, weighing silicate cement, epoxy resin, curing agent, and composite fiber, and mixing them with the foam obtained in step S1 to obtain the core layer raw material; S3. According to the required thickness of the composite board, determine the distance between the two sides of the calcium silicate boards that are away from each other, fill the core layer raw materials between the two calcium silicate boards, remove the mold after the test piece is formed for 1 day, and perform a compression test after standard curing for 28 days to obtain a high-strength composite board; The calcium silicate board facing is the outer surface of the high-strength composite board, and the surface of the calcium silicate board close to the core layer is a rough surface.
[0026] Embodiment 3: A high-strength composite board comprises a core layer and calcium silicate boards arranged on both sides of the core layer, wherein the core layer comprises the following raw materials in parts by weight: 90 parts of silicate cement, 6 parts of foaming agent, 35 parts of epoxy resin, 15 parts of curing agent and 25 parts of composite fiber, wherein the composite fiber comprises modified ramie fiber and modified brucite fiber twisted together.
[0027] Wherein, the epoxy resin is bisphenol A epoxy resin.
[0028] The preparation method of modified ramie fiber is as follows: S1. Take ramie fiber and soak it in 5% sodium hydroxide solution for 5 hours; S2, soaking the ramie fiber after the alkali treatment in a glycidyl acrylate grafting solution containing benzophenone for 24 hours, placing the soaked ramie fiber on a glass plate, pressing it with a glass sheet, and performing UV ultraviolet light grafting treatment; S3. The grafted ramie fiber was extracted by Soxhlet extraction for 10 hours, then treated in a 5% by volume ethylenediamine solution for 8 hours, then immersed in a 5% by volume nitric acid solution for 8 hours, and dried to obtain the modified ramie fiber.
[0029] The preparation method of modified brucite fiber is: S1, taking brucite fiber, adding sodium salt of dioctyl sulfonate succinate to disperse it, then performing ultrasonic treatment, washing it with deionized water, drying it and setting it aside; S2. Weigh 3% of the coupling agent by weight of the dry sample of brucite fiber, mix it evenly with the brucite fiber obtained in S1, and bake it in an oven at 100°C for 5 hours to obtain modified brucite fiber.
[0030] The preparation method of the composite plate comprises the following steps: S1, weighing a foaming agent, mixing the foaming agent with water in a mass ratio of 1:30 to prepare a foaming aqueous solution, and preparing the mixed foaming aqueous solution into foam using a foaming machine; S2, weighing silicate cement, epoxy resin, curing agent, and composite fiber, and mixing them with the foam obtained in step S1 to obtain the core layer raw material; S3. According to the required thickness of the composite board, determine the distance between the two sides of the calcium silicate boards that are away from each other, fill the core layer raw materials between the two calcium silicate boards, remove the mold after the test piece is formed for 1 day, and perform a compression test after standard curing for 28 days to obtain a high-strength composite board; The calcium silicate board facing is the outer surface of the high-strength composite board, and the surface of the calcium silicate board close to the core layer is a rough surface.
[0031] Comparative Example 1: A high-strength composite board, the high-strength composite board is different from Example 3 only in that no silicate cement is added.
[0032] Comparative Example 2: A high-strength composite board, the high-strength composite board is different from Example 3 only in that no foaming agent is added.
[0033] Comparative Example 3: A high-strength composite board, the high-strength composite board is different from Example 3 only in that no epoxy resin is added.
[0034] Comparative Example 4: A high-strength composite board, the high-strength composite board differs from Example 3 only in that no composite fiber is added.
[0035] Comparative Example 5: A high-strength composite board, the high-strength composite board is different from Example 3 only in that modified ramie fiber is not added.
[0036] Comparative Example 6: A high-strength composite board, the high-strength composite board is different from Example 3 only in that modified brucite fiber is not added.
[0037] Comparative Example 7: A high-strength composite board, the high-strength composite board is different from Example 3 only in that the ramie fiber is not modified.
[0038] Comparative Example 8: A high-strength composite board, the difference between the high-strength composite board and Example 3 is that the brucite fiber is not modified.
[0039] Comparative Example 9: A high-strength composite board, the high-strength composite board is different from Example 3 only in that the ramie fiber is not subjected to ultraviolet light treatment.
[0040] The composite boards obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-9 were subjected to performance tests to measure the comprehensive performance of the composite boards. The results are shown in Table 1.
[0041] Table 1 Performance parameters of the composite boards obtained in Examples 1-3 and Comparative Examples 1-9 Group Tensile strength / MPa Oxygen Index Elongation at break / % Example 1 189 30 20 Example 2 188 30 20 Example 3 190 30 20 Comparative Example 1 173 24 16 Comparative Example 2 178 25 18 Comparative Example 3 171 25 18 Comparative Example 4 141 16 13 Comparative Example 5 151 24 15 Comparative Example 6 152 24 15 Comparative Example 7 153 20 14 Comparative Example 8 151 21 14 Comparative Example 9 143 19 14 In summary, the ramie fiber that is UV-grafted with glycidyl acrylate, then aminated and nitrated contains N-OH. When preparing the composite board, the modified ramie fiber reacts with the epoxy group during the composite process of the epoxy resin, and the ramie fiber and the epoxy resin are connected by chemical bonds, and the interfacial viscosity effect is improved, thereby improving the mechanical properties of the composite board, and enhancing the tensile strength and impact resistance of the composite board. In addition, after the modified ramie fiber is composited with the epoxy resin to make a composite board, there is obvious carbonization during the combustion process, which promotes the esterification of cellulose hydroxyl groups, and the generated cellulose ester decomposes into carbon, so that the composite board has a good flame retardant effect.
[0042] The modified brucite fiber has good compatibility with epoxy resin and is firmly bonded. The silane-modified brucite nanofiber fills the molecular gap of epoxy resin and improves the impact resistance of the composite material.
[0043] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength composite plate, characterized in that: The composite board comprises a core layer and calcium silicate boards arranged on both sides of the core layer. The components of the core layer include the following raw materials in parts by weight: 80-100 parts of silicate cement, 4-10 parts of foaming agent, 30-40 parts of epoxy resin, 10-20 parts of curing agent and 20-30 parts of composite fiber. The composite fiber comprises modified ramie fiber and modified brucite fiber twisted together.
2. The high-strength composite plate according to claim 1, characterized in that: The preparation method of modified ramie fiber is as follows: S1. Take ramie fiber and soak it in 5% sodium hydroxide solution for 5 hours; S2, soaking the ramie fiber after the alkali treatment in a glycidyl acrylate grafting solution containing benzophenone for 24 hours, placing the soaked ramie fiber on a glass plate, pressing it with a glass sheet, and performing UV ultraviolet light grafting treatment; S3. The grafted ramie fiber was extracted by Soxhlet extraction for 10 hours, then treated in a 5% by volume ethylenediamine solution for 8 hours, then immersed in a 5% by volume nitric acid solution for 8 hours, and dried to obtain the modified ramie fiber.
3. The high-strength composite sheet material according to claim 2, characterized in that: The preparation method of the modified brucite fiber is: S1, taking brucite fiber, adding a dispersant to disperse it, then performing ultrasonic treatment, washing it with deionized water, drying it and setting it aside; S2. Weigh 3% of the coupling agent by weight of the dry sample of brucite fiber, mix it evenly with the brucite fiber obtained in S1, and bake it in an oven at 100°C for 5 hours to obtain modified brucite fiber.
4. The high-strength composite plate according to claim 3, characterized in that: The epoxy resin is one of bisphenol F epoxy resin, Novolac epoxy resin, bisphenol A epoxy resin or trimethylolpropane epoxy resin.
5. The high-strength composite plate according to claim 3, characterized in that: The dispersant is sodium salt of dioctyl sulfonate succinate.
6. The high-strength composite plate according to claim 3, characterized in that: The preparation method of the composite plate comprises the following steps: S1, weighing a foaming agent, mixing it with water to prepare a foaming aqueous solution, and preparing the mixed foaming aqueous solution into foam using a foaming machine; S2, weighing silicate cement, epoxy resin, curing agent, and composite fiber, and mixing them with the foam obtained in step S1 to obtain the core layer raw material; S3. According to the required thickness of the composite board, determine the distance between the two calcium silicate boards on the sides away from each other, fill the core layer raw materials between the two calcium silicate boards, remove the mold after the test piece is formed for 1 day, and perform a compression test after standard curing for 28 days to obtain a high-strength composite board.
7. The high-strength composite plate according to claim 6, characterized in that: The calcium silicate board facing is the outer surface of the high-strength composite board, and the surface of the calcium silicate board close to the core layer is a rough surface.
8. The high-strength composite plate according to claim 6, characterized in that: The mass ratio of the foaming agent to water is 1:30.